Publicidade e ciência: narrativas na tv aberta - SOUZA, Weverton Raiol Gomes de (Universidade Federal do Pará, 2017)
The objective of this dissertation is to understand how science is used in the narratives of advertisements broadcasted, between June and September of 2013, on TV Liberal and Record Belém broadcasters, both located in Belém, Pará. Our proposal is an outcome of the research “Representations of Women Scientist at Brazilian TV and on Teenagers Imaginary”, in which we perceived the occurrence of the utilization of science on advertisements in the program schedule of free-to-air TV. Using the data collected in that research, we made a new corpus of 83 advertisements aiming to analyze how science configure the advertising narratives. With the research and bibliographic review, we saw that advertising is heavily articulated to the market and our day-to-day lives, revealing itself as a mediation of communicational processes and a model constructor (TOALDO, 2005; GOMES, 2008; PIEDRAS, 2009; TRINDADE, 2012; MOTTA, 2013). To analyze the use of science in these narratives and discuss the relation that this use stablishes on society, we follow the analytic proposal of Motta (2013) that consists on seven acts. These analytic acts allow us to decompose and recompose the narratives focusing on the processes of communication that pass through television advertisements. We identified and discussed nine strategies of science utilization on the construction of advertising narratives, which are: (i) the scientific component; (ii) the scientific environment; (iii) the invitation to experimentation; (iv) the relation with innovation; (v) fiction and reality; (vi) the scientific animations and illustrations; (vii) the specialist and scientist characters; (viii) the celebrity characters; (ix) and the non-specialist characters. Those strategies stablish a notion that the scientific knowledge is a source of solutions to everyday problems by providing a creation and innovation environment capable of generating technologies that promote new social practices and are incorporated to the daily lives of the social subjects.